Youth and sexuality 1978 - Student study - Lewin, Bo (Uppsala University, 1984)
A cooperation project between the department of sociology at Uppsala University and the clinic of school gynecology in Uppsala, the purpose of which is to illustrate youths´ attitude to and experience of sexuality. The study-population consists of two groups, one of patients at the clinic of school gynecology and one of students who have not been in contact with the clinic. Both groups have answered identical questionnaires about personal data, information on sex, sexual attitudes, knowledge about sex, sexual experiences, contraceptives/use, knowledge, attitudes, feelings about sex and attitudes to sexual behaviour.

A cooperation project between the department of sociology at Uppsala University and the clinic of school gynecology in Uppsala, the purpose of which is to illustrate youths´ attitude to and experience of sexuality. The study-population consists of two groups, one of patients at the clinic of school gynecology and one of students who have not been in contact with the clinic. Both groups have answered identical questionnaires about personal data, information on sex, sexual attitudes, knowledge about sex, sexual experiences, contraceptives/use, knowledge, attitudes, feelings about sex and attitudes to sexual behaviour.
Ungdom och sexualitet 1978 - Studentstudien
Keywords: Gender and gender roles; Kön och könsroller; Youth; Ungdomar; Social Sciences; Samhällsvetenskap